Sfaturile lui Matei Al Mirelor către Alexandru Iliaș: tematică, retorică, limbaj - Anca Mihaela Sapovici (Revista de Istorie și Teorie Literară)
Written at the beginning of the 17th century by the abbot of the Dealu Monastery, the Epirot Matthew, Honorary Metropolitan of Myra in Asia Minor and addressed to Alexandru Iliaş (1616–1618), the prince of Wallachia, the Advices represents the second literary success of the parenetic species in the Romanian space, after the Theachings of Neagoe Basarab to his son Theodosius. In his creative approach, Matthew reported at a well-established tradition, cultivated since Antiquity and throughout all the history of the Byzantine Empire. In analyzing this work, we therefore considered not only the Byzantine parenetic tradition, but also its ties with this “tutelary presence” (Dan Horia Mazilu) from the history of the Romanian literature represented by the Teachings of the Wallachian Prince. Moreover, the linguistic phenomena illustrated within the Advices of Matthew of Myra highlight a socio-linguistic phenomenon with a rich illustration during the Phanariot period: the codeswitchings between Greek and Romanian. Thus, Matthew is one of the precursors of cultural and linguistic facts which the massive presence of the Greek ethnic element in the Romanian countries has favored since the first decades of the 17th century.